PENGARUH MODEL DISCOVERY LEARNING DISERTAI MEDIA GAMBAR TERHADAP KOGNITIF SISWA KELAS VII MTs BAHRUL ULUM TAHUN PEMBELAJARAN 2014/2015 - Fitriani, Hesti (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This research aims to know whether or not the effect of discovery learning model with picture media Â of the cognitive class VII MTs Bahrul Ulum. Type of research is a quasi experimental design with randomized control group pre test post test design. The population in this research were all students of class VII. The research sample class VII-A as the experimental class and the class VII-B as the control class. Data collection techniques in this research is a test instrument in the form of multiple choice questions. Data analysis techniques for hypothesis testing using t test. The results showed the average value of learning outcomes is the experimental class 79,14 and control class 72,57. Based on the hypothesis testing results, obtained t = 2,38, while ttable to significant level of 5% with n = 27 obtained table = 1,70. With the result that obtained tcount> ttable it can be concluded that there are significant discovery model of learning with picture media of the cognitive class VII MTs Bahrul Ulum.